The principle of equality and non-discrimination in the human rights debate: equal treatment or equal outcomes? / Prof. Madya Dr. Nik Salida Suhaila Nik Saleh - Nik Saleh, Nik Salida Suhaila (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Convention on the Elimination of All Forms of Discrimination against Women 1979 (the Women's Convention) Is an International human rights treaty that focuses specifically on equality between women and men in all areas of life. It defines discrimination against women and sets up an agenda for national action to end such discrimination. In its Title, the Convention underscores states' obligation to prohibit discrimination against women. Under the Convention, equality Is non-discrimination, and discrimination against women violates the principles of equality of rights and respect for human dignity. In the Preamble, the Convention explicitly acknowledges that 'extensive discrimination against women continues to exist' and emphasizes that such gender discrimination Violates the principles of equality of rights and respect for human dignity'.